2017
DOI: 10.3389/fcimb.2017.00227
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Profiling of High-Density Giardia Foci Encysting in the Murine Proximal Intestine

Abstract: Giardia is a highly prevalent, understudied protistan parasite causing significant diarrheal disease worldwide. Its life cycle consists of two stages: infectious cysts ingested from contaminated food or water sources, and motile trophozoites that colonize and attach to the gut epithelium, later encysting to form new cysts that are excreted into the environment. Current understanding of parasite physiology in the host is largely inferred from transcriptomic studies using Giardia grown axenically or in co-cultur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 109 publications
5
45
0
Order By: Relevance
“…Experiments in vivo further showed a reduced uptake of L-phenyl-alanine, L-lysine and L-aspartic acid in the intestines of infected swiss albino mice and a significant drop in the transport of L-alanine and glycine in mice (Anand et al, 1982 ). Giardia also scavenges the gut lumen for lipids including cholesterol (Pham et al, 2017 ), and secretes enzymes involved in phospholipids remodeling and scavenging fatty acids (Ma'ayeh et al, 2017 ). Cholesterol, specifically, is required for lipid raft formation and cholesterol starvation induces encystation (Yichoy et al, 2011 ; Mendez et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Experiments in vivo further showed a reduced uptake of L-phenyl-alanine, L-lysine and L-aspartic acid in the intestines of infected swiss albino mice and a significant drop in the transport of L-alanine and glycine in mice (Anand et al, 1982 ). Giardia also scavenges the gut lumen for lipids including cholesterol (Pham et al, 2017 ), and secretes enzymes involved in phospholipids remodeling and scavenging fatty acids (Ma'ayeh et al, 2017 ). Cholesterol, specifically, is required for lipid raft formation and cholesterol starvation induces encystation (Yichoy et al, 2011 ; Mendez et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…We also noted that the encystation-related genes are among the most highly expressed genes in G. muris trophozoites in vivo (Fig. S3c, Table S1b), similar to G. intestinalis infection in mice [42, 43].…”
Section: Resultsmentioning
confidence: 67%
“…In response to IECs, both Giardia isolates released proteins involved in cyst wall formation ( Fig 6 ) and these proteins were not detected in axenic culture indicating that host cells provide the signal to initiate encystation. Interestingly, in a recent study that investigated transcriptional changes in bioluminescent WB isolate trophozoites from high density foci in the mice intestines, the authors reported the up-regulation of encystation, oxidative stress and metabolic genes (carbohydrate, protein, lipid and nucleoside base metabolism) [ 83 ]. Herein, we show that the protein products for many of up-regulated genes in that study are being released into the interaction medium.…”
Section: Discussionmentioning
confidence: 99%
“…So far, most studies of Giardia -host cell interactions have been performed with simplified models using a small selection of human cell lines but it will be important to follow up these results using more complex in vitro host systems like enteroids [ 119 ]. This can be complemented by in vivo experiments of secreted proteins in mice where trophozoites are mixed with early encysting cells [ 83 ]. Thus, Giardia interaction with IECs is an intricate process and further understanding of this cross-talk could be the key for understanding giardiasis.…”
Section: Discussionmentioning
confidence: 99%